2015
DOI: 10.1177/1066896915570660
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ameloblastoma of the Mandible With Unusual Granular Cell Component

Abstract: Ameloblastomas can present in various clinical and histomorphologic patterns. The granular cell variant accounts for only 3.5% to 5% of ameloblastomas. The aim of this case report is to present an example of ameloblastoma with unusual granular cell component, affecting a 63-year-old woman, in which both the inner and peripheral layers of follicles composed exclusively by eosinophilic granular cells. Assessment of the immunohistochemical and histochemical profile of the lesion was performed and the challenges o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…GCA is diagnosed by the presence of granular cells, which usually occur within the central area of tumor and progressively replace the stellate reticulum. [ 11 ] Our case also showed similar features. Ultrastructurally, it has been revealed that the lysosome accumulation in these cells provides the characteristic granularity.…”
Section: Discussionsupporting
confidence: 73%
“…GCA is diagnosed by the presence of granular cells, which usually occur within the central area of tumor and progressively replace the stellate reticulum. [ 11 ] Our case also showed similar features. Ultrastructurally, it has been revealed that the lysosome accumulation in these cells provides the characteristic granularity.…”
Section: Discussionsupporting
confidence: 73%
“…Ameloblastoma is a locally aggressive epithelial odontogenic benign neoplasm, which has several different microscopic variants. [1][2][3] It is divided into three groups solid, peripheral and cystic (unicystic). The most common location is the posterior mandible.…”
Section: Introductionmentioning
confidence: 99%
“…4 Granular cytoplasmic changes are seen in the stellate reticulum regions of the ameloblastomatous follicles and interlacing cords and nests and it's a rare variant. In peripheral ameloblastic cells,g ranular changes can also be seen 1,6 this case report aimed to present a rare challenging case of ameloblastomain a 16-year-old male in the posterior aspect of the mandible. Case Report: A male of 16-year was referred for evaluation of the painless expansion on the left lower jaw region to the Department of Oral and Maxillofacial Pathology of Institute of Dental Sciences On intraoral examination there was a swelling in the posterior area of left mandible extending from 36 to 43 region.…”
Section: Introductionmentioning
confidence: 99%